CHIPICA (CHIPS SKIN CASSAVA) UTILIZING CASSAVA SKIN WASTE INTO HEALTHY PROCESSED PRODUCTS - Sunarko, Asep; Ranita, Ranita; Fivtyaningsih, Nurul; Wahidah, Nurin Nisa; Nasyifa, Kharisma Agustin (Sentra Kekayaan Intelektual dan Inovasi Teknologi (INOTEK) Universitas Sains Al-Qur'an, 2024)
Cassava is a people’s plant that is known throughout Indonesian and is a tropical annual tree. Cassava skin waste is a part of cassava that is generally not used and is wasted. In this case what is meant is the skin, so it becomes waste. There are two types of skin in this skin, namely inner skin and outer skin. This inner skin will be used as raw material for making healthy product, namely cassava skin chips. Cassava skin, which consists of a thin, brown outer layer of epidermis and a rather thick inner layer of dermis, has a high carbohydrate content which can be used as a new food source for humans.